Penerapan Konseling Individu Dengan Pendekatan Logotherapy Untuk Meningkatkan Kepercayaan Diri Pada Remaja Penyandang Disabilitas Fisik ( Studi Kasus Pada Klien “D” Di Sentra Budi Perkasa Palembang ) - Yolanda Yolanda; Zhila Jannati; Hartika Utami Fitri (Journal of Innovative and Creativity, 2025)
This study is entitled "Implementation of Individual Counseling with a Logotherapy Approach to Increase Self-Confidence in Adolescents with Physical Disabilities (Case Study of Client 'D' at the Budi Perkasa Center, Palembang)." This study aims to determine the client's self-confidence before being given a logotherapy approach, the process of implementing individual counseling using a logotherapy approach, and an overview of changes in self-confidence after being given a logotherapy approach to client "D." This type of research is field research (field research) using a qualitative approach and case study method, in which the researcher gathers in-depth information from several sources. Data collection techniques used were observation, interviews, and documentation. Meanwhile, data analysis techniques used in this study were pattern matching, data explanation, and time series analysis. The results of this study indicate that after undergoing the counseling process four times in one month with several stages of counseling implementation: the initial stage, the activity stage, and the final stage, positive changes were observed in client "D." Through the logotherapy approach, the client showed increased self-confidence, such as being more courageous in expressing opinions, demonstrating an attitude of confidence in one's abilities, and starting to be active in social activities with the surrounding community.